O-014 Intra-arterial cone beam CT angiography for the precise anatomic localization of intracranial and spinal arteriovenous fistulas. (12th July 2011) - Ansari, S; Hurley, M; Shaibani, A; Bendok, B; Soltanolkotabi, M; Chaudhry, N; Pandey, A; Gemmete, J
Abstract : Purpose: Cone beam CT angiography (CBCTA) provides enhanced vascular imaging for neurointerventional treatment planning, particularly of intravascular stents, thromboemboli, in-stent stenosis, and calcifications. In conjunction with traditional digital subtraction angiography (DSA) and 3D-DSA techniques, intra-arterial CBCTA offers superior contrast resolution to delineate the adjacent cross sectional anatomy and soft tissue architecture. We evaluated this technique and its efficacy in delineating the subtle arteriovenous anatomy of dural/pial arteriovenous fistulas (AVFs) for treatment planning purposes. Materials and Methods: We performed a retrospective review of intracranial and spinal dural/pial arteriovenous fistulas that underwent diagnostic DSA and intra-arterial CBCTA procedures at two large academic institutions. CBCTA scanning was performed with flat detector rotational angiography (Artis Zee Biplane, Siemens); 496 projection frames were acquired over a 200 degree arc (18 s rotation time, 80 kV, 260 mAs). Planar and 3D reconstructions (overlapping 0.5 mm and 5 mm slice thickness) were evaluated on an independent workstation (Leonardo). We studied patient demographics, presentations, classification/anatomic localization of AVFs, CBCTA technique, treatment, and complications. Neurointerventionalists/neurosurgeons involved in the diagnosis and treatment of these lesions graded any relevant improvement (0 or 1) in anatomic localization, treatment planning, or altered management derived from the CBCTA technique. Results: 20 patients (16:4 male, mean age 62 years) underwent 21 CBCTA procedures. Intracranial AVFs were classified as dural Cognard type 1 (n=3), type 2b, type 3 (n=7), and metameric dural/pial (n=2) presenting with transient ischemic attacks, headaches, pulsatile tinnitus, dizziness, or intracranial hemorrhages (n=4). Spinal AVFs were limited to dural Anson-Spetzler type 1 (n=9) presenting with cervical subarachnoid hemorrhage, intramedullary hemorrhage, neck pain, progressive upper and lower extremity weakness/paresthesias, and bladder/bowel dysfunction. CBCTA techniques ranged with respect to intra-arterial diluted contrast (30–50%) injections in the CCA, ICA, ECA, VA, middle meningeal, intercostal and lumbar arteries; rates of 0.3–3.0 ml/s and total volumes of 3.0–66 ml. A single CBCTA procedure was scanned using lower resolution and radiation dose with faster 8 s acquisition, but still providing accurate AVF localization. Significant improvement in anatomic mapping of AVFs was observed with CBCTA in 21/21 (arterial feeders, arteriovenous junction, venous drainers, or cross sectional localization), corresponding with an improved treatment plan in 12/21, and altering management or treatment in 4/21. Subsequently, these lesions were treated with Onyx/NBCA liquid embolization (n=12), coil embolization (n=2), microsurgical clipping (n=4) and radiation (n=1) with two patients refusing treatment. Two post-procedural complications included intracranial hemorrhage and myocardial infarction, but no complications were attributed to the CBCTA technique. Conclusion: We present a novel application of intra-arterial CBCTA as an adjunct to DSA for the precise anatomic localization of intracranial or spinal dural/pial AVFs. The impact of this technique allows for unparalleled cross-sectional mapping of arteriovenous pathology, assists in treatment planning most notably for microsurgical or radiation treatment, and can potentially alter patient management.